ORGANIZATION OF UKRZALIZNYTSIA’S INTELLECTUAL MANAGEMENT POWER SUPPLY COMPUTER ARCHITECTURE (Transport systems and technologies, 2018)
A modified computer architecture of intelligent management railroad electricity supply, designed to optimization the use of equipment by decentralization databases is proposed.
Keywords: computer architecture, intelligent, information, electricity, railways.